Modern business analytics practical data science for decision-making - Taddy, Matt (McGraw Hill Education, 2023)
The practice of data analytics is changing and modernizing. Innovations in computation and machine learning are creating new opportunities for the data analyst: exposing previously unexplored data to scientific analysis, scaling tasks through automation, and allowing deeper and more accurate modeling"--